Isolation and diagnosis of Bacillus types of locally prepared juices in Mosul - May Abdulqadir; Adeba Shareef (College of Education for Pure Sciences, 1970)
Abstract In this study genus Bacillus was isolated from locally prepared beverages in Mosul city, 64 samples of these juices were collected randomly from different places of the city. The results showed contamination of these juices by different species of the genus Bacillus. The most prevalent species was B. cereus followed by B. subtilis, other Bacillus spp. Were also isolated including B. mycoides , B. coagulans, B. megaterium, B. sphaericus , and the most contaminated type of juice were grapes and orange juices. The results also showed that the pH of the juices from which Bacillus spp. were isolated ranged between 1-5, this results declares the ability of the Bacillus isolates to grow at a acidic pH.